Pituitary Hormonal Disturbances in Aneurysmal Subarachnoid Hemorrhage - Moura, Jose Carlos de; Azevedo, Hildo Rocha Cirne de; Valença, Marcelo Moraes; Vidal, Claudio Henrique Fernandes; Moura, Samuel Miranda de; Rodrigues, Mateus de Sousa (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objective The objective of the present study was to assess the hormonal alterations that occurred in patients with subarachnoid hemorrhage.Methods This is a case series with 21 patients diagnosed with subarachnoid hemorrhage of aneurysmal etiology up to 30 days after the ictus. The following hormonal measurements were performed in these patients: cortisol, GH, testosterone, prolactin, estradiol, FSH, LH, FSH, T3, T4 and free T4. The hormonal results of the cases were compared with the results of twelve volunteers from the control group and correlated with findings in brain tomography, cerebral angiography, Hunt-Hess scale, and vasospasm.Results The main altered hormones were cortisol (52.6%), GH (42.9%) and TSH (28.6%). There was a trend towards more severe cases in the following groups of patients: Hunt-Hess scale > 2, Fisher scale > 1, aneurysmal topography in the anterior communicating artery and those who had vasospasm.Conclusion The present study observed the tendency of pituitary hormonal changes in patients with subarachnoid hemorrhage of aneurysmal etiology, corroborating the need for dosage of hormones from the hypothalamic-pituitary axis in the management of these cases.
Keywords: pituitary gland; pan-hypopituitarism; subarachnoid hemorrhage; hormone abnormalities; intracranial aneurysm